PEMANFAATAN SAMPAH ANORGANIK SEBAGAI MEDIA PEMBELAJARAN DI MTsN SAFINATUSSALAMAH AL-MUNAWARAH - Nuraini Fatmi; Iryana Muhammad (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2021)
This research was conducted with a team of lecturers from Malikussaleh University with the aim of realizing environmental-based learning through the use of waste as a learning medium that sharpens the creativity of teachers and students. This research was conducted at Madrasah Tsanawiyah Safinatussalamah Al-Munawarah. Dayah Safinatussalamah Al-Munawarah is located in Blang Panyang Village, Muara Satu District, Lhokseumawe City. The time of the research was carried out on August 9, 2021 and the place of research was at Madrasah Tsanawiyah Safinatussalamah Al-Munawarah. The population in this study were all MTsN students at the Safinatussalamah Al-Munawarah Islamic Boarding School and the sample was the 1st grade students of MTsN Safinatussalamah Al-Munawarah. The research uses a 'qualitative' approach. The research conducted is descriptive. The instruments in this study were observation sheets and documentation. Data analysis techniques used in this study: (1) Data Collection, (2) Data Reduction, (3) Data Verification, (4) Drawing Conclusions. The results of the study can be concluded that this activity teaches students to love the environment by utilizing inorganic waste and making inorganic waste as a product of learning media can also increase student creativity and learning outcomes, this is because students better understand the concept of learning by seeing and working through learning media.